Addressing xenophobia in South Africa : drivers, responses and lessons from the Durban untold stories - Ngcamu, Bethuel Sibongiseni; Mantzaris, Evangelos (Emerald Publishing, 2022)
Focusing on a prominent episode of anti-immigrant violence in the Durban area of the KwaZulu-Natal province, Addressing Xenophobia in South Africaidentifies the hidden, less addressed dimensions and catalysts of Xenophobia in South Africa.